The Effect of Islamic Private Debt Securities Rating Changes On Firm's Common Stock Returns - Mod Asri, N.; Abdul Karim, Z.; Shahimi, S.; Abdullah Al-Hadi, A. (Universiti Sains Islam Malaysia, 2024)
This paper examines the effect of Islamic private debt securities (IPDS) rating changes on the firm's common stock returns. It will provide the evidence of relationship between bonds rating and stocks return based on the traded IPDS rated by MARC and RAM, and common stock monthly price of listed firms in KLSE. Based on several different measures of abnormal return, the findings are consistent with the preposition that bond downgrading conveys information to common stockholders. As for bond upgrading, the stock price adjustments were statically insignificant in the month of announcement.